The Chinese Education Movement in Malaysia - Ang, Ming Chee (CLACSO, 2021)
This article explores why and how a minority social movement persists despite persistent constraints placed upon it by a majority-dominated State. The Chinese education movement has been one of the largest, longest, and most sustained social movements in Malaysia. Sociological, economic, and demographic changes of the Chinese community along with domestic political struggles revolving around the ethnic question have influenced the fluctuation of movement trajectory over time. The movement has sustained its activities and received moral and material support from the Chinese communities, despite persistent constraints by the government, scarcity of resources and lack of support from others Malaysian population. This article argues that constraints imposed by the State have been utilized by the social movement organization to mobilize support from the masses, and thus became the most significant factors that have sustained the movement. The article will first look into the evolution of the social movement and analyze the dynamic interaction between the State and the challengers from various perspectives, including the current status update of the social movement organizations and activities organized to sustain continuous collective action. In addition to the analysis of the movement’s achievements, this article will also explain the State’s reaction towards the movement and the measures undertaken to constrain or terminate the movement.